Students' Error in Solving Word Problems in One-Variable Linear Equation Material at SMP Islam Darul Ulum Ulum based on Gender - Yaqin, Nurul; Fa’ani, Arini Mayan (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
Errors are deviations made by students towards the actual results (predetermined answers). Errors in learning are divided into three parts, namely conceptual errors, procedural errors, and technical errors. One of the factors that affect learning mathematics is gender. This study aims to describe the errors of male and female students in solving word problems in the material of One-Variable Linear Equations (PLSV). This research method uses a qualitative approach with a descriptive method. The subject selection technique was carried out by classifying students based on gender, so that 2 male students and 2 female students were obtained whose middle-test score was below 75. Then for the data collection technique, a paper-word problem-test is used, interviews, and think aloud . The analysis of the validity of the data in this study uses triangulation methods, namely the paper-based test, think aloud and interview methods. The results of this study show that male students experience errors in solving word problems of the One-Variable Linear Equation (PLSV) material on conceptual and procedural errors, while female students experience errors in solving one-variable linear equation (PLSV) material word problems on procedural errors.